PENGARUH KETERAMPILAN KEWIRAUSAHAAN DAN KARAKTERISTIK INDIVIDU TERHADAP KEBERHASILAN USAHA PADA USAHA MIKRO DAN KECIL DI PERUMAHAN INDOGREEN, CITEUREP BOGOR - Adyas, Dasmansyah; Kurniawan, Rudy (Economicus, 2018)
This study aims to determine the effect of entrepreneurial skills and individual characteristics on the success they manage a business, especially small and micro entrepreneurs who open a business in Indogreen housing, Citeurep Bogor District. In this research the object is the entrepreneurs who numbered 50 people with saturated sample method. The data used in this study is the primary data derived from the questionnaire distribution. While the data analysis using Multiple Regression analysis technique.The findings of this study are the two variables tested both partially and simultaneously. In the test terminated R square value there are results of 0.670 or 67% of business success can be explained by entrepreneurial skills and the remaining individual characteristics of 33% by other variables not examined.